The evaluation of catholyte treatment on the colour and tensile properties of dyed cotton, polyester and polyamide 6,6 fabrics - Cronjé, Natasha (University of the Free State, 2015)
Colour is one of the most significant factors in the appeal and marketability of textile products. Cotton, polyester and polyamide 6,6 are the most prominent groups of fibres used in the world. A Life Cycle Assessment done on textile products revealed that the area of greatest environmental impact is the consumer use phase, due to the laundering habits for the care of these products over its life span. With the development of electrochemically activated water (Catholyte) and some research done to suggest it might be an environmentally friendly alternative detergent for laundering; the environmental impact during the consumer phase can therefore be considerably scaled down. The influence of Catholyte on the colourfastness of textiles is, however, unknown. Thus it was the aim of this study to determine the influence of Catholyte on certain colourfastness properties of dyed cotton, polyester and polyamide 6,6 textile fabrics. The sulphur, direct, reactive and azoic dyed cotton, disperse dyed polyester and acid dyed polyamide 6,6 textile fabrics were laundered (AATCC 61) with Catholyte, detergent and filtered water at 40C and 60C for five, ten, twenty or fifty cycles respectively. Wash fastness and staining (AATCC Evaluation Procedure 6) were measured instrumentally with a Konika Minolta Spectrophotometer 2300d using illuminant 10 standard observer. Colourfastness to rubbing, dry and wet (AATCC 8), as well as tensile strength (SANS 1092) was also evaluated. The colorimetric data obtained was converted to Gray scale ratings (AATCC Evaluation Procedure 12). The results indicate that laundering with Catholyte caused slightly less Gray scale values as opposed to laundering with detergent, with regards to sulphur and direct black dyed cotton. Higher wash fastness was observed when reactive black and direct red dyed cotton samples were laundered with Catholyte, as opposed to laundering with detergent. When laundering disperse red dyed polyester, acid red dyed polyamide, azoic orange, reactive red, blue, violet and green dyed cotton, with both Catholyte and detergent indicated similar wash fastness results. Staining results indicate that laundering sulphur black, reactive black, red, blue and violet, azoic orange dyed cotton and acid red dyed polyamide with detergent resulted in less staining than laundering with Catholyte. Laundering direct black dyed cotton resulted in less staining when laundered with Catholyte, compared to laundering with detergent. Regardless of laundering the disperse red dyed polyester, direct red and reactive green dyed cotton with either Catholyte or detergent, similar staining results were observed. The influence of both Catholyte and detergent on the colourfastness to dry rubbing of sulphur black, direct black and reactive black and red, azoic orange dyed cotton and acid red dyed polyamide were similar. Laundering the disperse red dyed polyester and the direct red, reactive green and blue dyed cotton, resulted in slightly higher colourfastness to dry rubbing when laundered with detergent. Laundering the reactive violet dyed cotton with Catholyte resulted in better colourfastness to dry rubbing when compared to laundering with detergent. Laundering the direct black, reactive black, red, blue, violet and green, azoic orange dyed cotton, disperse red dyed polyester and acid red dyed polyamide with Catholyte and detergent resulted in similar colourfastness to wet rubbing. Laundering the sulphur black and direct red dyed cotton with detergent resulted in slightly less colourfastness to wet rubbing when compared to laundering with Catholyte. Laundering sulphur black, reactive black and violet, direct red and azoic orange dyed cotton with detergent, caused greater loss in tensile strength as opposed to laundering with Catholyte. Laundering the direct black and reactive red, blue and green dyed cotton, disperse red dyed polyester, acid red dyed polyamide with Catholyte, caused greater loss in tensile strength.

Kleur is een van die belangrikste faktore in die aanloklikheid en bemarking van tekstielprodukte. Katoen, poliëster en poliamied 6,6 is die prominentste groepe van vesels wat in die wêreld gebruik word. ‘n Lewensiklus-analise wat op tekstielprodukte gedoen is, dui aan dat die verbruikersfase die grootste aandeel in omgewingsimpak het. Dit sluit wasgewoontes en versorging van tekstielprodukte in. Die ontwikkeling van elektrochemies-geaktiveerde water (Catholyte), tesame met navorsing wat aandui dat dit moontlik ‘n omgewingsvriendelike alternatief tot wasdetergente kan wees; kan dalk die omgewingsimpak gedurende die verbruikersfase aansienlik verminder. Die invloed van Catholyte op die kleurvastheid van tekstiele is egter onbekend. Dit was dus die doel van hierdie studie om die invloed van Catholyte op sekere kleurvastheid eienskappe van gekleurde katoen, poliëster en poliamied 6,6 tektielstowwe te bepaal. Die swael-, direk-, reaktief- en aso gekleurde katoen, dispersie gekleurde poliëster en suur gekleurde poliamied 6,6 tekstielstowwe is met Catholyte, detergent en filtreerde water by 40C en 60C vir vyf, tien, twintig of vyftig siklusse, onderskeidelik gewas (AATCC 61). Wasvastheid en vlekkking (AATCC Evaluasie Prosedure 6) is instrumenteel met ‘n Konika Minolta Spektrofotometer 2300d gemeet, en ‘n illuminant 10 standaard observeerder is gebruik. Kleurvastheid tot afvrywing, droog en nat (AATCC 8), asook treksterkte (SANS 1092) is geëvalueer. Die kolometriese data wat verkry is, is omgeskakel na Grysskaal waardes (AATCC Evaluasie Prosedure 12) toe. Die resultate dui aan dat om met Catholyte te was, effense laer Grysskaal waardes in vergelyking met detergent, ten opsigte van swael- en direk swart gekleurde katoen tot gevolg het. Hoër wasvastheid is opgemerk wanneer reaktief swart- en direk rooi gekleurde katoen met Catholyte gewas is, in vergelyking met dit wat met detergent gewas is. Wanneer dispersie rooi gekleurde poliëster, suur rooi gekleurde poliamied, aso oranje-, reaktief rooi-, blou-, violet- en groen gekleurde katoen, met beide Catholyte en detergent gewas is, is soortgelyke wasvastheid ondervind. Vlekresultate dui aan dat die swael swart-, reaktief swart-, rooi-, blou- en violet-, aso oranje gekleurde katoen en suur rooi gekleurde poliamied met detergent te was, minder gevlek het as om dit met Catholyte te was. Om direk swart gekleurde katoen met Catholyte te was het minder vlekking veroorsaak as om met detergent te was. Soortgelyke resultate is verkry deur dispersie rooi gekleurde poliëster, direk rooi en reaktief groen gekleurde katoen met Catholyte of detergent te was. Die invloed van Catholyte en detergent op die kleurvastheid tot afvrywing, droog, vir swael swart-, direk swart- en reaktiewe swart- en rooi-, en aso oranje gekleurde katoen was soortgelyk. Om die dispersie rooi gekleurde poliëster en direk rooi gekleurde, reaktief groen- en blou gekleurde katoen met detergent te was het beter kleurvastheid tot gevolg gehad. Om die reaktief violet gekleurde katoen met Catholyte te was het beter kleurvastheid tot afvrywing, droog, gehad vergeleke met detergent. Om die direk swart-, reaktief swart-, rooi-, blou-, violet- en groen-, aso oranje gekleurde katoen, dispersie rooi gekleurde poliëster en suur rooi gekleurde poliamied met Catholyte en detergent te was het soortgelyke vastheid tot afvrywing, nat, gehad. Om die swael swart- en direk swart gekleurde katoen met detergent te was het effens minder kleurvastheid tot afvrywing, nat, gehad in vergelyking om met Catholyte te was. Om die swael swart-, reaktief swart- en violet-, direk rooi- en aso oranje gekleurde katoen met detergent te was, het ‘n groter verlies in trektsterkte tot gevolg gehad as wanneer dit met Catholyte gewas is. Om die direk swart- en reaktief rooi-, blou- en groen gekleurde katoen, dispersie rooi gekleurde poliëster, suur rooi gekleurde poliamied met Catholyte te was, het ‘n groter verlies in treksterkte veroorsaak as om met detergent te was.
Thesis (Ph.D. (Consumer Science))--University of the Free State, 2015
Keywords: Colorfastness (Textiles); Resist-dyed textiles; Catholyte; Wash fastness; Colourfastness; Tensile strength; Textiles dyes